10 Myths about Psychosomatics - V. A. Soldatkin; S. V. Soldatkina (Медицинский вестник Юга России, 2023)
This article is devoted to the actual problems of psychosomatic medicine. Common myths are discussed, according to which only 7 psychosomatic diseases are known (restrictive interpretation), or alternatively, all human diseases are psychosomatic (expansive interpretation). The article presents a modern classification of psychosomatic disorders, information on predisposition to them, and highlights the main concepts of pathogenesis. Attention is devoted to the main forms of somatoform disorders, organic neuroses, nosogenic disorders, and the problem of hypochondria is illuminated. In this article attention is paid to the need for an integrated approach to the treatment of psychosomatic disorders, including the impact on both mental and somatic components. The requirements for the use of psychopharmacological drugs in psychosomatic medicine are given, emphasis is placed on the principle of «minimum sufficiency», which requires the use of minor doses of safe drugs that can cure the psychosomatic symptoms and are capable to treat the diagnosed mental disorders. The main non-drug methods aimed at correcting psychosomatic disorders are presented. The authors are convinced that in the field of psychosomatics the chances for successful diagnosis and therapy are given by the concept of «counter movement» – the interdisciplinary interaction of psychiatrists and internists, the essence of which is the urgent need for interdisciplinary cooperation of psychiatrists and internists, which increases the chances of successful assistance in such a complex and myth-rich field like psychosomatics.